Impact of Selected Asian Stock Market Movement on Indian Stock Market - Palanisamy, Varadharajan; Selvakumar, Joshua; G, Suganya (Center of Research and Innovation Strengthen LP2M UNM, 2024)
The involvement of people in the stock market has also increased in recent days. Thus, as a result, the volatility of the market has also increased. The profit-to-loss ratio on the stock market trade has also been on the lower side. The difficulties in the stock market have been unpredictable, thus upsetting the interests of the investors. This study compares the movement of the Indian stock markets (Sensex and Nifty) with six other major Asian stock markets (Japan, China, Hong Kong, Singapore, South Korea, and Taiwan) and tries to find the relationship between them. This study is done to check whether the movement of the major Asian stock markets is a predictor of the movement of the Indian stock markets. Statistical tools such as ordinary least squares, the Granger co-integration test, and a correlation matrix are used in this study to calculate the relationships. The result of this study will be helpful for stock market investors, particularly the short-term traders (intra-day traders) on the BSE and NSE.